2022
DOI: 10.1371/journal.pone.0263437
|View full text |Cite|
|
Sign up to set email alerts
|

Azithromycin consumption during the COVID-19 pandemic in Croatia, 2020

Abstract: Background During the initial phase of the COVID-19 pandemic, there was great enthusiasm for the use of azithromycin with or without hydroxychloroquine. Objectives We analyzed azithromycin consumption in Croatia in 2020 and compared this to the period 2017–2019. Methods Azithromycin consumption was evaluated using the IQVIA Adriatic d.o.o. database which collects data on azithromycin distribution from wholesale pharmacies to hospital and non-hospital pharmacies in Croatia. We analyzed data for the period f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
4
21
0
1
Order By: Relevance
“…Many clinical studies have shown that the use of azithromycin did not have any positive effect in the treatment of patients with COVID-19 infection ( Del Fiol et al, 2022 ). In the newer version of the guidelines for the treatment of patients with COVID-19, strong recommendations were made against the use of azithromycin alone and azithromycin in combination with hydroxychloroquine and colchicine ( Bogdanić et al, 2022 ; Del Fiol et al, 2022 ; Roche et al, 2022 ). Regarding inpatient settings, the hospital list of restricted antibiotics that require an approval from the designated infection control team when used consists of 15 antibiotics (piperacillin/tazobactam, cefuroxime, ceftazidime, ceftriaxone, cefotaxime, cefepime, imipenem/cilastatin, meropenem, ertrapenem, vancomycin, colistin, clarithromycin, moxifloxacin, ciprofloxacin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies have shown that the use of azithromycin did not have any positive effect in the treatment of patients with COVID-19 infection ( Del Fiol et al, 2022 ). In the newer version of the guidelines for the treatment of patients with COVID-19, strong recommendations were made against the use of azithromycin alone and azithromycin in combination with hydroxychloroquine and colchicine ( Bogdanić et al, 2022 ; Del Fiol et al, 2022 ; Roche et al, 2022 ). Regarding inpatient settings, the hospital list of restricted antibiotics that require an approval from the designated infection control team when used consists of 15 antibiotics (piperacillin/tazobactam, cefuroxime, ceftazidime, ceftriaxone, cefotaxime, cefepime, imipenem/cilastatin, meropenem, ertrapenem, vancomycin, colistin, clarithromycin, moxifloxacin, ciprofloxacin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the results of our study, in 2020 there was a decrease in consumption of first-generation cephalosporins and amoxicillin in Brazil, which was explained by a decrease in all respiratory infections except for COVID-19 [ 24 ]. The consumption of macrolides was significantly higher in 2020 compared to 2019 in all regions of the RS, which was also registered in all neighboring countries and globally [ 25 ]. The increased consumption of azithromycin is explained by its previously proven immunomodulatory and antiviral effect, which along with antibacterial effect protects against the worsening of viral infections [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of MDR and XDR pathogens is primarily due to the overuse of antibiotics. Azithromycin is one of the drugs excessively used during the COVID-19 pandemic globally [ 31 33 ], and the emergence of S . Typhi resistant to azithromycin has been reported in different parts of the world [ 9 , 34 ].…”
Section: Discussionmentioning
confidence: 99%